2009
DOI: 10.1118/1.3070585
|View full text |Cite
|
Sign up to set email alerts
|

Integral dose conservation in radiotherapy

Abstract: Treatment planners frequently modify beam arrangements and use IMRT to improve target dose coverage while satisfying dose constraints on normal tissues. The authors herein analyze the limitations of these strategies and quantitatively assess the extent to which dose can be redistributed within the patient volume. Specifically, the authors hypothesize that (1) the normalized integral dose is constant across concentric shells of normal tissue surrounding the target (normalized to the average integral shell dose)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…To define additional predictive factors we investigated the whole brain integral dose in patients without WBRT and found that more than 3 J was associated with a statistically significant increase in leukoencephalopathy. These findings are consistent with the observation that integral dose is relatively constant in concentric volumes despite increasing conformality around the target [58]. To our knowledge, this is the first report identifying a parameter to guide physicians in limiting leukoencephalopathy in patients treated with SRS (namely integral dose).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…To define additional predictive factors we investigated the whole brain integral dose in patients without WBRT and found that more than 3 J was associated with a statistically significant increase in leukoencephalopathy. These findings are consistent with the observation that integral dose is relatively constant in concentric volumes despite increasing conformality around the target [58]. To our knowledge, this is the first report identifying a parameter to guide physicians in limiting leukoencephalopathy in patients treated with SRS (namely integral dose).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Given consistent target coverage across patients, the relative spatial configuration of an OAR with respect to a target determines, to a large extent, the dose distribution of the OAR: OARs distant from the target are easy to spare, while proximal or overlapping OARs are difficult. 7 Several head-and-neck studies have used the overlap volume between an OAR and a target as a descriptor of the relative spatial configuration. [8][9][10][11] However, the overlap volume is not meaningful when the OAR and target do not overlap.…”
Section: Methodsmentioning
confidence: 99%
“…The dose calculation algorithm took into account primary radiation from the treatment machine and scattered radiation from the patient and from beam collimation, leakage, radiation, and lung heterogeneity. The integral dose may be considered the volume-weighted sum of the doses, the mean dose multiplied by the volume, or the total energy deposited (in joules [J]) (31)(32)(33).…”
Section: Radiation Dosimetrymentioning
confidence: 99%